Do epitáfio ao epitáfio fabuloso : parodiando identidades e reatualizando discursos - Pereira, Alécia Lucélia Gomes (2013)
The various discourses that circulate in society, to be materialized on the textual form, and are subject trace of truth wills that follow a regime of repeatability. With this, we find different discursive materiality, refracting the events and presenting statements already said. In this paper we produce gestures interpretation of the inscriptions around posthumous. It's about gender epitaph we turn our eyes, based on a reading of discursive practice that enables us to understand the meanings through the production conditions of utterances. Our study takes a look toward production of discourse epitáfico, official and fabulous, from the procedures used in his speeches, how they are organized and redistributed. Therefore, we, the light of the theoretical assumptions of Discourse Analysis of French line, the general objective, analyze the genre both in the epitaph "official" as in fabulous shape, as evidenced by observing the redefinition of gender through memory and discursive power relations that are involved in their sayings. The "new" epitaphs, to break the discursive order established in the original epitaphs, fall into a place unofficial, and utopian comic grotesque, inscribing new meanings through a subversive and weaving complaints glimpse wires in the text a socio-historical characteristic of postmodern thought.